2017
DOI: 10.21164/pomjlifesci.170
|View full text |Cite
|
Sign up to set email alerts
|

Fluorki w kościach człowieka – wybrane zagadnienia

Abstract: Długotrwała podaż fluoru prowadzi do fluorozy kostno-szkieletowej. Toksyczność fluorków (F⁻), nie tylko dla organizmu człowieka, ale i całego ekosystemu, powoduje, że niezbędne jest stałe monitorowanie ich zawartości w środowisku. W związku z tym istnieje konieczność kontrolowania stężenia fluorków u ludzi, szczególnie w tkance kostnej, która odzwierciedla długofalową kumulację tych związków. Celem pracy było określenie stężenia fluorków w kościach człowieka w zależności od czynników biologicznych i warunków ś… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Our study has shown that bone Mg levels of subjects aged between 75–87 years were significantly higher than in their younger counterparts aged 56–74. Analyzing the levels of F- in the femur of women from two age groups (>65 and <65 years old), Palczewska-Komsa et al [24] found that the former had a considerably higher concentration of the element than the latter one (525 and 275 mg∙kg −1 dm, respectively). In males, the concentration of fluorides in the femur showed an opposite pattern—those less than 65 years old showed higher F- levels than their older counterparts (552 and 268 mg∙kg −1 dm, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Our study has shown that bone Mg levels of subjects aged between 75–87 years were significantly higher than in their younger counterparts aged 56–74. Analyzing the levels of F- in the femur of women from two age groups (>65 and <65 years old), Palczewska-Komsa et al [24] found that the former had a considerably higher concentration of the element than the latter one (525 and 275 mg∙kg −1 dm, respectively). In males, the concentration of fluorides in the femur showed an opposite pattern—those less than 65 years old showed higher F- levels than their older counterparts (552 and 268 mg∙kg −1 dm, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Максимальне накопичення фтору при тривалому надходженні в організм людини виявлено в нирках [3], через які виводиться в середньому до 50% спожитого фтору. Не виведений фтор з організму у людини розподіляється між органами, зокрема, накопичується в кістках [4], дентині зубів, епіфізі та інших тканинах [3]. Токсичні дози фтору для людини варіюють в широких межах: для дорослих становлять 16-64 мг/кг, а для дітей -3-16 мг/кг [1,2].…”
unclassified